DAKWAH KENABIAN DAN KONSTRUKSI MASYARAKAT KHAYALAN - Ishak Hariyanto; Agus Dedi Putrawan (Universitas Islam Negeri (UIN) Mataram, 2018)
The Prophet's missionary journey as an arena for building a humanitarian system that is mutually acceptable and recognizes the values ??of human equality in the social system is still a deviation, even though life must embrace one another, accept unconditionally and respect human values. Acceptance of fellow humans seems to have become a deviation and even becomes collective amnesia in social life. This collective amnesia is present in human life without realizing that we live in it so that acceptance in the name of the man as a form of hablumminannas is like the construction of a mere imaginary society. The construction of imaginary societies has occurred in Medina as a social institution on the journey of prophetic preaching. Such things occur as a process of living systems; a process of establishing his identity as a social system in building the ideal society that has ever existed on this earth. The Madinah community is a society based on a collective agreement stated in a charter, commonly known as the charter of Medina. Relations between groups are built based on the breath of acceptance among others, because of the awareness of the similarity of the nature and dignity of human beings. Why Medina is referred to as a normal social system identity, not because of the intersubjectivity; acceptability of humans and humans built from all components of the social system is always in communication and mutual action.